2020
DOI: 10.1177/0008125620968609
|View full text |Cite
|
Sign up to set email alerts
|

Open Innovation’s “Multiunit Back-End Problem”: How Corporations Can Overcome Business Unit Rivalry

Abstract: This article examines the “multiunit back-end problem” of open innovation based on a case study of the Banque Populaire Caisse d’Epargne (BPCE) Group, a large French bank with two business units. The multiunit back-end problem occurs when internal business units who consider themselves rivals are asked to collaborate for the success of an open innovation initiative. BPCE failed several times to use external startups to accelerate its digital transformation due to rivalry between its internal business units. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It is also important to note that there is an additional way how open innovation can learn from the literature on managing coopetition. Some research with an open innovation lens such as Seran and Bez (2021) shows that internal competition between business units were jeopardizing open initiatives, and -of particular concern to this paper -cooperative start-up engagements.…”
Section: Research Opportunity 5: the Coopetitive Inside-in Open Innov...mentioning
confidence: 98%
“…It is also important to note that there is an additional way how open innovation can learn from the literature on managing coopetition. Some research with an open innovation lens such as Seran and Bez (2021) shows that internal competition between business units were jeopardizing open initiatives, and -of particular concern to this paper -cooperative start-up engagements.…”
Section: Research Opportunity 5: the Coopetitive Inside-in Open Innov...mentioning
confidence: 98%
“…Moreover, the extant OI literature has failed to provide answers to some of its most pressing challenges, such as the "Multiunit Back-End Problem" -an issue that occurs when internal business units who consider themselves rivals are asked to collaborate for the success of an OI initiative. 22 For instance, due to rivalry between internal business units, the large French bank group Banque Populaire Caisse d'Epargne (BPCE) failed numerous times to collaborate with external startups to accelerate its digital transformation. This is closely related to the presence of knowledge boundaries (often called silos) among business units, where local actors have the ability and motivation to limit the sharing of knowledge under their control.…”
Section: Oi and The Role Of Cvcmentioning
confidence: 99%
“…Other legacy obstacles are inherent in the company culture. New research sheds light on the difficulties of getting the front end of innovations talk to the back end (Chesbrough, 2020; Seran & Bez, 2021). Seran and Bez for example found that a major obstacle for seizing the innovations in the organization was rivalry between two business units in the back end.…”
Section: Contingencies and Bumps In The Roadmentioning
confidence: 99%